Metastasis, Risk Factors and Prognostic Significance of Splenic Hilar Lymph Nodes in Gastric Adenocarcinoma - Chen, Xiao-Long (Public Library of Science, 2014)
BACKGROUND: The metastatic rate and risk factors of splenic hilar (No.10) lymph nodes (LNs) in gastric adenocarcinoma were still variable and uncertain, and the prognostic significance of No.10 LNs was also controversial. The aim of this retrospective study was to analyze the metastatic rate, risk factors and prognostic significance of No.10 LNs in gastric adenocarcinoma. METHODS: From August 2007 to December 2011, 205 patients who were diagnosed with primary gastric adenocarcinoma and underwent total or proximal gastrectomy plus No.10 LNs dissection in West China Hospital were enrolled. Clinicopathological features and survival outcomes were retrospectively analyzed. RESULTS: Mean numbers of harvested LNs and metastatic LNs were 34.8±12.6 (15–73) and 8.7±10.8 (0–67), respectively. The proportion of cases with positive No.10 LNs was 8.8% (18/205). In all 204 dissected No.10 LNs, 47 LNs (23.0%) were metastatic. In 52.2% (107/205) patients, the dissected splenic hilar tissues were histologically determined as only fat tissues but without LNs structure. Histological evidence of LNs structure was found in 98 (47.8%) patients with 18.4% (18/98) metastatic No.10 LNs. In multivariate logistic regression analysis, metastasis of No.10 LNs was significantly correlated with No.4sa LNs (p = 0.010) and pN stage (p = 0.012). Regarding survival analysis, 199 (97.1%) patients were followed up (0.6–74.8 months). In all patients with R0 resection, metastatic No.10 LNs caused significantly worse prognosis both in Kaplan-Meier (p = 0.006) and Cox regression analysis (p = 0.031). CONCLUSIONS: Although the metastatic rate of No.10 LNs was 8.8%, dissection of No.10 LNs might be meaningful due to the poor prognosis of positive cases. And attentions should be also paid to its correlated factors including pN stage and No.4sa LNs.